Mobilizações do @escolasempartidooficial no instagram: análise netnográfica da interação on-line a partir do modelo dialogal da argumentação - Bacelar, Ana Paula de Sousa (2021)
This work aims to describe and interpret the dynamics of comments recorded on posts of the movement “Escola Sem Partido/School Without Party” on Instagram. On social media, the definition of the teacher’s professional identity is analyzed based on the interactions promoted by the posts available at @escolasempartidooficial. In the context of cyberculture, the non-presential interpersonal communication is a unique place for interaction, where users make use of strategies and specific resources for the creation of arguments and the mix of dissenting perspectives. Seen in this term, using the theoretical- -methodological apparatus of the Dialogal Model of Argumentation, developed by Christian Plantin, we envision the professional identity of teachers looking upon two dimensions: self-recognition (ethos) and hetero-recognition (image). We start from the ideia that the shock of these two conflicting dimensions establishes an argumentative situation that, in the wake of the dissent, allows other issues to be brought into question wihtin an argumentative framework established by the interactional game. To that end, we search for theoritical basis in discourse studies (BAKHTIN, 2003, 2011; CHARAUDEAU, 2011; MAINGUENEAU, 2006; GOFFMAN, 2002), in the theoretical framework of Argumentation and Rhetoric (PLANTIN, 2002, 2008, 2009, 2016; GRACIO, 2010, 2013; PERELMAN, 1996; PERELMAN and OLBRECHTS-TYTECA, 2005; REBOUL, 2004; AMOSSY, 2005, 2017) and in the specific literature of digital media (LÉVY, 2000; RECUERO, 2009; DIONÍSIO, 2011; ROJO, 2012; NEIVA, 2013; SLOAN, QUAN-HAASE, 2017; KOZINETS, 2014). This is a mixed methodology netnographic study. The selected corpus, called Post_ESP, consists of 9 publications and 482 comments. From the adoption of the definition as a category of analysis, we articulate functional elements and qualifying elements. The initial results of the analysis demonstrate that the teaching identity, when called into question, opens new questions, founding a chain of interaction organized from the topics of the comments.